The Link between Quality of Governance and Stock Market Performance: International Level Evidence - Isaac Boadi; Hayford Amegbe (European Journal of Government and Economics (EJGE), 2017)
The present study investigates the link between quality of governance and stock market performance within the context of international markets. The study employed the Fixed Effect model using 23 countries with complete relevant data for the period spanning from 1996 to 2014. The study reveals that, quality of governance as captured by Voice and Accountability, Political Stability and Absence of Violence, Government Effectiveness, Regulatory Quality, Rule of Law and Control of Corruption significantly affect stock market performance. Varying effects are produced when the countries are decomposed into income classifications. What is more, the findings and suggestions of this study suggest that quality of government significantly affect foreign direct investment and could have interesting policy implications. The main value of this paper is to examine the link between quality of governance and stock market performance within the context of international markets.
Keywords: 330; Stocks market; Quality of Governance; Fixed Effect; Country-Level